Rancang Bangun Aplikasi Gatepass dan Exit Clearance Berbasis Web - Purnamasari, Dwi Amalia; Karisa, Veve (Jurnal Ilmu Komputer, 2024)
Rapid technological advancements have transformed the operational processes of companies, shifting from manual to technology-dependent systems. PT Cladtek Bi-Metal Manufacturing faces the need to leverage technology, particularly in the gatepass and exit clearance processes for all employees. Previously, these processes are managed manually, resulting in lengthy procedures, accumulation of physical documents, potential documentation errors for audit purposes, and excessive paper usage with environmental impacts. Gatepass is used for employees requiring permission to leave the company during working hours, while exit clearance is a mandatory procedure for employees before permanently leaving the company, involving the return of company assets. By transitioning to digital recording, this study successfully produced a web-based application using the prototype method.The results of this study certainly make a positive contribution by simplifying the gatepass and exit clearance process for all employees, by transitioning from manual to digital recording.